delvin

50 Reputation

5 Badges

2 years, 148 days

MaplePrimes Activity


These are replies submitted by delvin

@Thomas Richard 

 Yes, I am not very familiar with the site and I am a beginner in Maple software. I need this equation with its answers and graph for my project. Now I use the dsole command to solve it to see if it gets the same answer?
Is it possible that it cannot be solved with this command because it is nonlinear?
My system hangs when running this command code and unfortunately it doesn't stop, I have to turn off the system.
Thank you very much for taking the time to answer my question.
Thank you for your guidance.

 

@Thomas Richard 

  Thank you dear Richard,

@Thomas Richard 

 Unfortunately, it did not answer.

 

@mmcdara

 thanks

@tomleslie 

  

  Thank you for taking time out of your busy day.
   Sincerely,

   delvin

@rcorless 

   The equation is correct, but I didn't pay attention, I wrote some in my own language,sorry.

@Rouben Rostamian  

   Sorry, I was not paying attention.

      Thanks ocean.

@tomleslie 

 Ok, I want to check the different solutions of the equation.

 

  Thanks a million, You made my day.

 

@tomleslie 

   Thank osean very much for your time.

 "Because the answers are not what I want , The answers obtained are obvious."

m4.mw

@Joe Riel 

This is the code I wrote, but it didn't get a good answer

restart

with(student)

U := a[0]+sum(-a[i]*tanh(xi[n])^i, i = 1 .. 1)+sum(-b[i]*tanh(xi[n])^(-i), i = 1 .. 1)

a[0]-a[1]*tanh(xi[n])-b[1]/tanh(xi[n])

(1)

u(xi[n+1]) := a[0]-a[1]*(tanh(xi[n])+tanh(d))/(1+tanh(xi[n])*tanh(d))-b[1]*(1+tanh(xi[n])*tanh(d))/(tanh(xi[n])+tanh(d))

a[0]-a[1]*(tanh(xi[n])+tanh(d))/(1+tanh(xi[n])*tanh(d))-b[1]*(1+tanh(xi[n])*tanh(d))/(tanh(xi[n])+tanh(d))

(2)

u(xi[n-1]) := a[0]-a[1]*(tanh(xi[n])-tanh(d))/(1+tanh(xi[n])*tanh(d))-b[1]*(1+tanh(xi[n])*tanh(d))/(tanh(xi[n])-tanh(d))

a[0]-a[1]*(tanh(xi[n])-tanh(d))/(1+tanh(xi[n])*tanh(d))-b[1]*(1+tanh(xi[n])*tanh(d))/(tanh(xi[n])-tanh(d))

(3)

eq := c*(diff(U, xi))-(U^2+U*beta+alpha)*(u(xi[n+1])-u(xi[n-1]))

-((a[0]-a[1]*tanh(xi[n])-b[1]/tanh(xi[n]))^2+(a[0]-a[1]*tanh(xi[n])-b[1]/tanh(xi[n]))*beta+alpha)*(-a[1]*(tanh(xi[n])+tanh(d))/(1+tanh(xi[n])*tanh(d))-b[1]*(1+tanh(xi[n])*tanh(d))/(tanh(xi[n])+tanh(d))+a[1]*(tanh(xi[n])-tanh(d))/(1+tanh(xi[n])*tanh(d))+b[1]*(1+tanh(xi[n])*tanh(d))/(tanh(xi[n])-tanh(d)))

(4)

U := a[0]-a[1]*tanh(xi[n])-b[1]/tanh(xi[n])

a[0]-a[1]*tanh(xi[n])-b[1]/tanh(xi[n])

(5)

simplify(eq); fin1 := simplify(numer(%))

-2*(tanh(xi[n])^4*a[1]^2-a[1]*(beta+2*a[0])*tanh(xi[n])^3+(beta*a[0]+a[0]^2+2*a[1]*b[1]+alpha)*tanh(xi[n])^2-b[1]*(beta+2*a[0])*tanh(xi[n])+b[1]^2)*tanh(d)*((b[1]*tanh(d)^2-a[1])*tanh(xi[n])^2+2*tanh(xi[n])*tanh(d)*b[1]+tanh(d)^2*a[1]+b[1])

(6)

subs(tanh(xi[n]) = Psi, fin1); fin := simplify(%)

2*(Psi^4*a[1]^2-a[1]*(beta+2*a[0])*Psi^3+(beta*a[0]+a[0]^2+2*a[1]*b[1]+alpha)*Psi^2-b[1]*(beta+2*a[0])*Psi+b[1]^2)*((-Psi^2*b[1]-a[1])*tanh(d)^2-2*Psi*tanh(d)*b[1]+Psi^2*a[1]-b[1])*tanh(d)

(7)

for i from 0 to degree(fin, Psi) do EQ[i] := simplify(coeff(fin, Psi, i)) end do

2*a[1]^2*(-b[1]*tanh(d)^2+a[1])*tanh(d)

(8)

Eqs := {seq(EQ[i], i = 0 .. 6)}

Sol := solve(Eqs, {c, a[1], b[1]})

{c = c, a[1] = 0, b[1] = 0}

(9)

 

Download m3.mw

@acer 

okey

@dharr thanks an ocean

@dharr Thanks

NULL

restart;
with(PDEtools):


pde2:=-lambda*diff(y(xi),xi)+y(xi)*diff(y(xi),xi)+diff(y(xi),xi$2)=0;

-lambda*(diff(y(xi), xi))+y(xi)*(diff(y(xi), xi))+diff(diff(y(xi), xi), xi) = 0

(1)

 

NULL

phi(xi):=(p[1]*exp(q[1]*xi)+p[2]*exp(q[2]*xi))/(p[3]*exp(q[3]*xi)+p[4]*exp(q[4]*xi));
eval(phi(xi),[p[1]=I,p[2]=-I,p[3]=1,p[4]=1,q[1]=I,q[2]=-I,q[3]=I,q[4]=-I]);
simplify(%);
phi(xi):=%;
U(xi):=A[0]+sum(A[d]*phi(xi)^d,d=1)+sum(B[d]*phi(xi)^(-d),d=1);

(p[1]*exp(q[1]*xi)+p[2]*exp(q[2]*xi))/(p[3]*exp(q[3]*xi)+p[4]*exp(q[4]*xi))

 

(I*exp(I*xi)-I*exp(-I*xi))/(exp(I*xi)+exp(-I*xi))

 

-sin(xi)/cos(xi)

 

-sin(xi)/cos(xi)

 

A[0]-A[1]*sin(xi)/cos(xi)-B[1]*cos(xi)/sin(xi)

(2)

subs(y(xi)=U(xi),pde2);

-lambda*(diff(A[0]-A[1]*sin(xi)/cos(xi)-B[1]*cos(xi)/sin(xi), xi))+(A[0]-A[1]*sin(xi)/cos(xi)-B[1]*cos(xi)/sin(xi))*(diff(A[0]-A[1]*sin(xi)/cos(xi)-B[1]*cos(xi)/sin(xi), xi))+diff(diff(A[0]-A[1]*sin(xi)/cos(xi)-B[1]*cos(xi)/sin(xi), xi), xi) = 0

(3)
 

 

Download test1.mw

5 6 7 8 Page 7 of 8